2011
DOI: 10.1037/a0023098
|View full text |Cite
|
Sign up to set email alerts
|

Pattern specificity in the effect of prior Δƒ on auditory stream segregation.

Abstract: During repeating sequences of low (A) and high (B) tones, perception of two separate streams ("streaming") increases with greater frequency separation (Δƒ) between the A and B tones; in contrast, a prior context with large Δƒ results in less streaming during a subsequent test pattern. The purpose of the present study was to investigate what aspects of the context pattern are necessary for this context effect to occur. Simply changing the B-tone frequency without an alternating A tone present was not sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 74 publications
7
21
0
Order By: Relevance
“…Specifically, these studies have consistently found that listeners are more likely to report perceiving a test sequence as two separate streams when the preceding (or context) sequence contained a small Δƒ than when the context sequence contained a large Δƒ Snyder et al, 2008;Snyder, Holder, et al, 2009;Snyder & Weintraub, 2011). In addition to this contrastive effect of prior stimulation, a facilitative effect of prior judgment was also found, whereby listeners were more likely to report perceiving the test sequence as two separate streams if they had also reported perceiving the context sequence as two streams than if they had reported perceiving the context sequence as a single stream Snyder et al, 2008;Snyder, Holder et al, 2009).…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Specifically, these studies have consistently found that listeners are more likely to report perceiving a test sequence as two separate streams when the preceding (or context) sequence contained a small Δƒ than when the context sequence contained a large Δƒ Snyder et al, 2008;Snyder, Holder, et al, 2009;Snyder & Weintraub, 2011). In addition to this contrastive effect of prior stimulation, a facilitative effect of prior judgment was also found, whereby listeners were more likely to report perceiving the test sequence as two separate streams if they had also reported perceiving the context sequence as two streams than if they had reported perceiving the context sequence as a single stream Snyder et al, 2008;Snyder, Holder et al, 2009).…”
mentioning
confidence: 96%
“…It was also recently shown that the Δƒ of the previously presented sequence(s) and whether the listener perceived the previous sequence(s) as one stream or two have a major impact on subsequent perceptual judgments Snyder et al, 2008;Snyder, Holder, et al, 2009;Snyder & Weintraub, 2011). Specifically, these studies have consistently found that listeners are more likely to report perceiving a test sequence as two separate streams when the preceding (or context) sequence contained a small Δƒ than when the context sequence contained a large Δƒ Snyder et al, 2008;Snyder, Holder, et al, 2009;Snyder & Weintraub, 2011).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, Bendixen et al Bendixen et al, 2010) showed that the auditory system can utilize regular temporal patterns for sorting sounds into streams (see also Andreou et al, 2011;Rimmele et al, 2012;Snyder and Weintraub, 2011). However, while the regularities tested by Bendixen and colleagues Bendixen et al, 2010) extended the intervals during which listeners perceived the tone sequence in terms of two streams, they did not affect the length of the intervals during which listeners perceived the tone sequence as a single integrated stream.…”
Section: Introductionmentioning
confidence: 99%